Wortbilder und Übersetzungsbilder - Kubaszczyk, Joanna (Wydawnictwo Naukowe Uniwersytetu Im. Adama Mickiewicza W Poznaniu, 2011)
The monograph Word Images and Translation Images is a study of word formation and translation. The aim of the study is to verify the statement by Tabakowska (1993: 30) that “an important constituent of translation equivalence would be equivalence on the level of imagery”. The analysis shows how verbal images created originally in the source text by means of word formation change in the target text and why. The research is based on assumptions of cognitive linguistics and especially on Langacker’s concept of conventional imagery. As an instrument to explore the changes on the level of imagery in the target texts, three kinds of vividness, proposed by Fix (2002), are used: vividness of form, vividness of word meaning and vividness of generalization (the process of metaphoric figurativeness). In addition, the problem of mental images is considered and the question is asked whether the word images created by the word formation can evoke similar mental images shared by many language users. An experiment conducted on the reception of a poem by Baczyński seems to demonstrate that this is possible.